2021
DOI: 10.1111/epi.16868
|View full text |Cite
|
Sign up to set email alerts
|

Defining the latent period of epileptogenesis and epileptogenic zone in a focal cortical dysplasia type II (FCDII) rat model

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Kao et al . 31 recently studied epileptogenesis in a rat model of Depdc5-related FCD type II, and documented a similar progression of immature electrographic patterns towards mature forms of cortical discharges. Using both intermittent and continuous EEG monitoring, they found that mature patterns gradually emerge from brief runs of SW complexes that progressively last longer, and finally morph into well-formed SWDs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Kao et al . 31 recently studied epileptogenesis in a rat model of Depdc5-related FCD type II, and documented a similar progression of immature electrographic patterns towards mature forms of cortical discharges. Using both intermittent and continuous EEG monitoring, they found that mature patterns gradually emerge from brief runs of SW complexes that progressively last longer, and finally morph into well-formed SWDs.…”
Section: Discussionmentioning
confidence: 93%
“…Using both intermittent and continuous EEG monitoring, they found that mature patterns gradually emerge from brief runs of SW complexes that progressively last longer, and finally morph into well-formed SWDs. 31 Likewise, in the GAERS rat model of absence-type epilepsy, epileptiform activity gradually progresses during epileptogenesis. Oscillatory epileptiform discharges emerge first, become progressively intermingled with SW complexes, and finally shape into fully mature SWDs.…”
Section: Discussionmentioning
confidence: 99%
“…P16∼18 mice with three epidural screw electrodes were monitored for 8 h per day and then returned to the mother. Procedures for affixing electrodes in young rodents were performed as we previously described [8]. To detect the earliest seizures, a subset of <P14 mice were monitored for 3 h, two times every day, and then returned to the mother.…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR/Cas9 IUE manipulations via NHEJ and HDR are amenable to multiplexing—editing of multiple genes simultaneously (Chen et al., 2015; Mikuni et al., 2016). In addition to facilitating basic gene‐function studies, IUE‐mediated CRISPR/Cas9 genome editing has been used to model human diseases and assess specific patient variants such as loss‐of‐function variants in SPTAN1 seen in patients with early infantile epileptic encephalopathy type 5 (Hu et al., 2018; Kao et al., 2021; Lu et al., 2018; Ribierre et al., 2018; Wang et al., 2018). This is especially useful when modeling human disorders like FCD, with typified isolated regions of disorganized cortical neurons in an otherwise anatomically normal brain.…”
Section: Crispr/cas9 Genome Editing (Figure 2c)mentioning
confidence: 99%
“…This is especially useful when modeling human disorders like FCD, with typified isolated regions of disorganized cortical neurons in an otherwise anatomically normal brain. Whole brain transgenic mice do not recapitulate the isolated, clustered nature of dysplasia, but IUE of targeted regions of cortex does (Hu et al., 2018; Kao et al., 2021).…”
Section: Crispr/cas9 Genome Editing (Figure 2c)mentioning
confidence: 99%